Pneumococcal Phenotype and Interaction with Nontypeable Haemophilus influenzae as Determinants of Otitis Media Progression - Joseph A. Lewnard; Noga Givon-Lavi; Paula A. Tähtinen; Ron Dagan (AMER SOC MICROBIOLOGY, 2022)
All-cause otitis media (OM) incidence has declined in numerous settings following introduction of pneumococcal conjugate vaccines (PCVs) despite increases in carriage of nonvaccine pneumococcal serotypes escaping immune pressure. To understand the basis for the declining incidence, we assessed the intrinsic capacity of pneumococcal serotypes to cause OM independently and in polymicrobial infections involving nontypeable Haemophilus influenzae (NTHi) using samples obtained from middle ear fluid and nasopharyngeal cultures before PCV7/13 rollout. Data included samples from OM episodes (11,811) submitted for cultures during a 10-year prospective study in southern Israel and nasopharyngeal samples (1,588) from unvaccinated asymptomatic children in the same population. We compared data representing pneumococcal serotype diversity across carriage and disease isolates with and without NTHi coisolation. We also measured associations between the pneumococcal phenotype and the rate of progression from colonization to OM in the presence and absence of NTHi. Whereas pneumococcal serotype diversity was lower in single-species OM than in single-species colonization, levels of serotype diversity did not differ significantly between colonization and OM in mixed-species episodes. Serotypes differed roughly 100-fold in progression rates, and those differences were attenuated in polymicrobial episodes. Vaccine serotype pneumococci had higher rates of progression than nonvaccine serotypes. While serotype invasiveness was a weak predictor of the OM progression rate, efficient capsular metabolic properties-traditionally thought to serve as an advantage in colonization-predicted an enhanced rate of progression to complex OM. The lower capacity of nonvaccine serotypes to cause OM may partially account for reductions in all-cause OM incidence despite serotype replacement in carriage following rollout of PCVs.